Nutritional profile of amateur young swimmers: gender differences - Tauler, P.; Martinez, S.; Pasquarelli, B. N.; Moreno, C.; Romaguera, D.; Arasa, C.; Aguiló, A. (Archivos de medicina del deporte, 2008)
Nowadays, young athletes are subjected earlier to high intense training programs and competitions, which involve the need of getting good performance at the same time health level is maintained at a good standard. Adolescent athletes require specifi c nutritional support in order to maintain normal growth and physiological maturation as well as to cope with athletic performance The aim of this study was to evaluate the nutritional profi le of adolescent swimmers belonging to semi-professional teams. Thirty-six caucasian adolescent swimmers (22 boys and 14 girls) participated voluntarily in the study. Dietary intake and clinical biochemical parameters were determined. Energy intake, as well as protein intake, per kg of body weight was signifi cantly higher in males compared to females. On the other hand, females showed significantly greater polyunsaturated fatty acids intake compared to males. Energy as well as carotenes, vitamin A, vitamin E, vitamin D and folic acid intakes of males and females were below to their requirements. Women showed also inadequate intakes of iron and calcium. Oppositely, protein intake doubled the requirements of the study population. Serum iron and cholesterol related parameters were within the normal range for healthy people and no differences were found between genders. In conclusion, young swimmers participating presented low average total energy intake, excessive protein intake and lower intake of several micronutrients in both genders.